Theoretical analysis of the electrostatic interactions between charged polarisable particles - Brazil Lindgren, Eric (2017)
Theoretical approaches to calculating electrostatic interactions between charged particles of dielectric materials are presented and applied to diverse examples of electrostatic behaviour. The accuracy of numerical predictions based on the multipole expansion used in calculations of the electrostatic force is discussed. Strict corresponding convergence criteria are established, particularly when addressing problems involving materials with high dielectric constants, large differences in particles size and short inter-particle separation distances. An extensive study of various types of electrostatic interactions is undertaken, with greater stress on the circumstances in which rather counterintuitive events might exist, namely the attraction between like-charged particles, generally dependant on certain degrees of asymmetry in charge density and charge distribution on the surface of the interacting particles, and the repulsion between oppositely charged particles, which involves magnitudes of charge that are below some critical limit and the presence of a sufficiently polarisable medium. Several examples addressing experimental problems, notably the growth mechanism of aerosols in the atmosphere of Saturn’s moon Titan, and electrostatic self-assembly processes, are included. Many-particle dynamics simulations of electrostatically driven systems are finally presented through some selected scenarios.